1977
DOI: 10.1136/bjo.61.9.555
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral retinal ablation in the treatment of proliferative diabetic retinopathy: a three-year interim report of a randomised, controlled study using the argon laser.

Abstract: SUMMARY A randomised controlled trial is reported of 94 patients with a symmetrical proliferative diabetic retinopathy involving the optic disc, who were treated by a peripheral retinal ablation technique using the argon laser. A highly significant difference in mean cumulative deterioration of visual acuity and blindness was shown in all but the late stages of the disease process between treated and untreated eyes. The untreated eyes exhibited far worse results. The earlier photocoagulation is initiated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…In the more severely affected group (in which fibrous tissue is found on the optic disc) we have found improvement in visual acuity and regression of disc new vessels in 30% and 70% of eyes respectively. Our findings are in accord with Hercules et al (9), who found improvement in vision and regression of disc new vessels in patients with retinal fibrosis but no evidence of traction. These authors noted no improvement where macular traction already existed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the more severely affected group (in which fibrous tissue is found on the optic disc) we have found improvement in visual acuity and regression of disc new vessels in 30% and 70% of eyes respectively. Our findings are in accord with Hercules et al (9), who found improvement in vision and regression of disc new vessels in patients with retinal fibrosis but no evidence of traction. These authors noted no improvement where macular traction already existed.…”
Section: Discussionsupporting
confidence: 82%
“…The prognosis is worse still if the new vessels arise from the optic disc, the risk of blindness rising to 70% over five years (5,10). In recent years a number of randomised controlled clinical trials have shown conclusively that in diabetic retinopathy both argon laser and xenon arc photocoagulation are effective in causing regression of new vessels (9,11) and in improving or maintaining visual acuity (6,7,9,11). In these studies the advantage of treatment was found to be particularly striking in eyes with new vessels arising from the optic disc.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The Diabetic Retinopathy Study (DRS) recommended that treatment consists of 800-1600 argon laser burns of 500 mm size to the peripheral retina in a scatter fashion. 1 However, previous studies have shown that PRP is a painful procedure for most patients.…”
Section: Introductionmentioning
confidence: 99%
“…For eyes with diffuse oedematous maculopathy at baseline, focal treatment alone had been given in 28.9% (11), grid treatment alone in 65.7% (25) and both grid and focal treatment in 5.3% (2). For those eyes where the diffuse oedema had improved and proliferative retinopathy had not developed, the median number of burns given was 125 (44-3218, SD 647).…”
Section: Treatment Givenmentioning
confidence: 99%